THE EFFECTIVENESS OF USING ANIMATION IN TEACHING PRESENT CONTINUOUS TENSE; A CASE STUDY OF SEVENTH GRADE STUDENTS OF SMP KARTIYOSO SEMARANG - Wahid Hamzah (Universitas PGRI Semarang, 2013)
This research discusses the use of animation to teach present continuous tense. The objectives of this final project are to know the student’s ability of the seventh grade of SMP Kartiyoso Semarang taught using animation pictures and without using animation and to know if there is any significant different of the student’s ability in understanding present continuous tense with and without using animation of the seventh grade students of SMP Kartiyoso Semarang. The population in this research is the seventh grade students of SMP Kartiyoso, Semarang in the academic year 2012/2013. They are 106 students. The writer uses one group or class to be observed. The writer uses one group as sample which consists 30 students. A test as an instrument is used to collect the data. The writer uses multiple choice test in this research. The writer asks the students to answer the questions by crossing (x) a, b, c, or d. In conclusion, teaching present continuous tense using animation as media is more effective than teaching present continuous tense without animation. It could be seen from the result of the test where students’ score taught using animation is higher than those taught without using animation. It can be seen that the t-test is higher than the t-table (2.419 > 2, 002). To improve the quality of teaching learning English, the teacher must be able to create the way to arouse the students’ interest in following his teaching. It would be better for the teacher to use media to teach the students according to their need.